Kajian Model Estimasi Volume Limpasan Permukaan, Debit Puncak Aliran, dan Erosi Tanah dengan Model Soil Conservation Service (SCS), Rasional Dan Modified Universal Soil Loss Equation (MUSLE) (Studi Kasus di DAS Keduang, Wonogiri) - Murtiono, Ugro Hari (Universitas Muhammadiyah Surakarta, 2008)
Hydrologic modelling has been developing and it is usefull for basic data in managing water resources. The aim of the reseach is to estimate volume runoff, maximum discharge, and soil erosion with SCS, Rational, and MUSLE models on Keduang Watershed. Explain the data analysis, and flow to get the data. SCS parameters model use are: runoff, rainfall, deferent between rainfall runoff. The deferent rainfall between runoff relationship kurva Runoff Coefisient (Curve Nunmber/CN). This Coefisient connected with Soil Hydrology Group (antecedent moisture content/AMC), landuse, and cultivation method. Rational parameters model use are: runoff coefisient, soil type, slope, land cover, rainfall intensity, and watershed areas. MUSLE parameters model use are: rainfall erosifity (RM), soil erodibility (K), slope length (L), slope (S), land cover (C), and soil conservation practice (P). The result shows that the conservation service models be applied Keduang Watershed, Wonogiri is over estimed abaut 29.54 %, Rational model is over estimed abaut 49.96 %, and MUSLE model is over estimed abaut 48.47 %.